1997
DOI: 10.1046/j.1471-4159.1997.69051840.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Neuronal Kinesin Heavy Chain Is Developmentally Regulated in the Central Nervous System of the Rat

Abstract: Abstract:The kinesin family of motor proteins comprises at least two isoforms of conventional kinesin encoded by different genes: ubiquitous kinesin, expressed in all cells and tissues, and neuronal kinesin, expressed exclusively in neuronal cells. In the present study, we have analyzed the expression of the two kinesin isoforms by immunochemistry at different stages of development of the rat CNS. We have found that the level of expression of neuronal kinesin is five to eight times higher in developing than in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
5
9
0
Order By: Relevance
“…These neurons are "regenerating," even in the adult brain (Paxinos, 1995). We observed high expression of KIF5B in cultured hippocampal and spinal cord neurons (data not shown), and previous studies have revealed that the expression of kinesin was upregulated in the developing rat CNS (Vignali et al, 1997) and disruption of KIF5B using antisense oligonucleotides reduced the neurite length and inhibited vesicle transport in cultured hippocampal neurons (Ferreira et al, 1992). These findings collectively suggest that the expression of KIF5B is highly upregulated in neurons at the stage of axonal elongation.…”
Section: Roles Of the Three Kif5s In Neuronssupporting
confidence: 85%
See 1 more Smart Citation
“…These neurons are "regenerating," even in the adult brain (Paxinos, 1995). We observed high expression of KIF5B in cultured hippocampal and spinal cord neurons (data not shown), and previous studies have revealed that the expression of kinesin was upregulated in the developing rat CNS (Vignali et al, 1997) and disruption of KIF5B using antisense oligonucleotides reduced the neurite length and inhibited vesicle transport in cultured hippocampal neurons (Ferreira et al, 1992). These findings collectively suggest that the expression of KIF5B is highly upregulated in neurons at the stage of axonal elongation.…”
Section: Roles Of the Three Kif5s In Neuronssupporting
confidence: 85%
“…KIF5A was expressed evenly among neurons, with similar pattern of distribution to its human homolog, nKHC (Navone et al, 1992;Niclas et al, 1994;Vignali et al, 1996Vignali et al, , 1997. On the other hand, expression of KIF5C was highly upregulated, especially in mature lower motor neurons, indicating its important roles in the maintenance of motor neurons rather than in their formation.…”
Section: Roles Of the Three Kif5s In Neuronsmentioning
confidence: 84%
“…The age of vulnerability is associated with a period of motor learning in humans and corresponds to a developmental stage of high synaptic plasticity in primate (71) and rodent (72) neostriatum. In rat brain, kinesin-I is enriched in elongating neurites and growth cones (73,74). Similarly, we found enrichment of both kinesin and torsinA in growth cones of cultured rat cortical neurons.…”
Section: Nx(t/s) Asnsupporting
confidence: 72%
“…Although the precise significance of this heterogeneity in conventional kinesin subunits from brain is unknown, it likely reflects functional differences (13). Supporting this idea, kinesin-1s showed significant differences in their tissue distribution (25,26), developmental expression profiles (43), and transport rates (18), and specific KLC isoform variants are found in association to different MBOs (11,12,44). From these observations, it became apparent that determining the precise composition of conventional kinesin from brain represented a critical step toward an understanding of mechanisms underlying the targeting of conventional kinesin to different MBOs.…”
Section: Discussionmentioning
confidence: 97%